MARKETING COMMUNICATION STRATEGY OF AIRPLANE TICKET SALES AT PT.TX TOUR AND TRAVEL GORONTALO BRANCH - Ade Safitri Biludi; Andi Subhan; Salma P Nua; Ramansyah Ramansyah (Universitas Swadaya Gunung Jati, 2023)
Communication in the business world is significantly considered capable of overcoming various problems faced by a company.Â Various strategies are needed to survive every business challenge today.Â Communication strategies play a significant role in marketing goods or services. This study aims to find and analyze the marketing communication strategy of airplane ticket sales at PT TX Tour and Travel Gorontalo Branch. This study applies a descriptive qualitative method. Data collection is done through observation and interviews. The result of this study is that the owner and employees of the company have carried out some marketing communication strategies (Morissan, 2010), namely: 1) Direct marketing through direct offers to potential customers of products or services. 2) Sales promotion is carried out through discounts for a minimum purchase of 20 airplane tickets. 3) Advertising is carried out actively in the form of promotions on social media. 4) Personal selling carried out is in the form of face-to-face communication with customers walking in directly. 5) Public Relations is only carried out through public relations activities with a general pattern because PT TX Tour and Travel Gorontalo Branch does not have a special public relations division. Marketing communication applied by PT TX Tour and Travel Gorontalo Branch has the strength to survive amid development and competition. However, PT TX Tour and Travel Gorontalo Branch still has weaknesses that need to be improved again with new, more innovative strategic planning techniques to face competition in the travel tourism business.Â Keywords: marketing communication, airplane ticket sales